The Relationship Between Moral Distress With Level of Burnout on Nurses in Intensive Care Room at the dr. Soebandi Hospital Jember - Siswoyo Siswoyo; Kholid Rosyidi Muhammad Nur; Faizatul Ulya (Faculty of Nursing, Universitas Jember, 2020)
Moral distress is defined as psychological disequilibrium and negative feelings that results from recognizing an ethically appropriate action, yet not taking it because of such barriers. This causes an increase workload of nurses in the intensive care room, resulting burnout that affects nurses, patients and health care providers. This study aimed to analyze the relationship between moral distress and the level of burnout in intensive care room nurses at the dr. Soebandi Hospital Jember. This study used a quantitative descriptive observational analytic with the approach cross sectional design selected 47 nurses as respondents used total sampling. Data collected by Measure of Moral Distress Scale - Healthcare Professionals (MMD-HP) and Maslach Burnout Inventory (MBI). The results revealed that most respondents experienced low moral distress (85.1%) and low burnout (61.7%). The bivariate analysis showed with spearman test that p-value was < 0.001 (α = 0.05; r = 0.531). There was a relationship between moral distress and the level of burnout in intensive care room nurses at the dr. Soebandi Hospital Jember with moderate and positive relationship strength. A healthy work environment plays an important role in the low level of moral distress and burnout, if there are staff skilled in communication, good collaboration between people or professions, effective decision making, proper staffing, recognition and leadership.